2015
DOI: 10.1371/journal.pone.0120667
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Simulation Framework for the Prediction of Strategic Noise Mapping and Occupational Noise Exposure Using the Random Walk Approach

Abstract: Strategic noise mapping provides important information for noise impact assessment and noise abatement. However, producing reliable strategic noise mapping in a dynamic, complex working environment is difficult. This study proposes the implementation of the random walk approach as a new stochastic technique to simulate noise mapping and to predict the noise exposure level in a workplace. A stochastic simulation framework and software, namely RW-eNMS, were developed to facilitate the random walk approach in noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…A strategic noise map provided information such as the location of noise sources, the pattern of noise distribution, and the noise circumstances (Bite et al, 2005;Zannin et al, 2013) , which could be utilised to examine permissible limits, decide on noise abatement strategies and design the optimal placement for new machines (Lee et al, 2008;Tsai et al, 2009). In addition, the strategic noise maps could indicate high noise exposure areas, thereby allowing noise practitioners to utilise the noise map as a reference to decide on areas for conducting personal noise exposure measurements (Han et al, 2015). In Malaysia, compliance with the Factory and Machinery Act (Noise Exposure) Regulations is required for all industries as TAN LEE HANG, LIM MING HAN, LEE YEE LING, TAN OOI KUAN a guide to monitor noise levels in their workplaces (Factories and Machineries Act, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strategic noise map provided information such as the location of noise sources, the pattern of noise distribution, and the noise circumstances (Bite et al, 2005;Zannin et al, 2013) , which could be utilised to examine permissible limits, decide on noise abatement strategies and design the optimal placement for new machines (Lee et al, 2008;Tsai et al, 2009). In addition, the strategic noise maps could indicate high noise exposure areas, thereby allowing noise practitioners to utilise the noise map as a reference to decide on areas for conducting personal noise exposure measurements (Han et al, 2015). In Malaysia, compliance with the Factory and Machinery Act (Noise Exposure) Regulations is required for all industries as TAN LEE HANG, LIM MING HAN, LEE YEE LING, TAN OOI KUAN a guide to monitor noise levels in their workplaces (Factories and Machineries Act, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to conduct further research on the noise exposure problem and noise control strategies in this industry. Current noise mapping practice still relies on unstandardised approaches for the development of noise maps for this industry (Han et al, 2015). The latest noise mapping prediction technique (Han et al, 2015) has confidentially demonstrated its high accuracy and reliability through its proposed stochastic simulation method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of simulation tools is appearing more and more often in the assessment of physical factors, in conjunction with the assessment of emerging risks in the workplace. Predicting and evaluating noise, as one of the major environmental factors, through the use of software support is a highly topical issue, which can be confirmed by the contributions in [ 7 , 8 , 9 , 10 ], which deal primarily with mapping, simulation, and assessment of the impact of noise on workers. In addition to assessing noise as a physical factor in the work environment, simulation tools are used to assess thermal well-being at workplaces, as reported in [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For typical acoustic simulations using either the Finite Element Method or the Boundary Element Method, the exact locations of the noise sources and their respective noise profiles would be required. Researchers often need to resort to statistical or operational research methods such as the random walk approach, 5 the Monte Carlo method, 6 and the discrete event simulation method. 7 A review of the analysis methods and mitigation measures can be found in the work by Wu.…”
Section: Introductionmentioning
confidence: 99%